TECHNOLOGICAL FACTORS OF RUNNING DURABILITY OF CAST INSTRUMENT - F. I. Rudnitski (Литьë и металлургия)
Conformities of forming of the high-speed steels structure depending on crystallization conditions are studied. Findings have a great importance for development of the technological process of the cast instrument production.